AKTIVITAS TEH (AIR SEDUHAN ) DAUN KELOR SEBAGAI HEPATOPROTEKTOR PADA TIKUS PUTIH JANTAN YANG DIINDUKSI FORMALIN DOSIS TOKSIK - Ida Bagus Suaskara; Ni Gusti Ayu Ermayanti; Martin Joni; I Ketut Ginantra; Anastesya . (Program Studi Biologi Universitas Udayana, 2024)
An attempt to avoid formalin side effects of toxin dose contained in food is to administer hepatoprotectant. Moringa is one of the food sources that functions as a hepatoprotector. The purpose of this study was to determine the activity of Moringa leaf tea (steeping water) as an antioxidant and hepatoprotector in male white rats induced with formalin doses of toxicity. The method used in this study was a randomized group design (RGD). The liver damage barrier test used a formalin-induced male white rat model (0.100 ml/BB) as a negative control, tea (steeping water) of Moringa leaves was given at a dose of 50, 75, 100 mg/BB once a day and the administration of aquades as a positive control for 7 days. The formalin-induced group of mice showed a significant increase in SGPT, SGOT and MDA values compared to positive controls. Orally administering Moringa leaf tea (steeping water) can weaken or decrease the increase in SGPT, SGOT and MDA values in male rats compared to formalin-induced significantly. So that giving tea from steeping water Moringa leaves can be an alternative as drinking water after meals. Keywords: toxic, SGOT, SGPT, MDA